Pre-hospital assistance by ambulance in the context of coronavirus infections - Amanda Ferreira Araujo; Eric Rosa Pereira; Sabrina da Costa Machado Duarte; Priscilla Valladares Broca
ABSTRACT Objective: To reflect on the safe care exercised by the pre-hospital care team by emergency ambulance in times of coronavirus infection. Method: A reflection and description of how to provide safe care to the patient and the professional during pre-hospital care in times of coronavirus infection. Results: To ensure the health of all those involved in the care, health professionals who work in pre-hospital care by emergency ambulance should use the recommended Personal Protective Equipment (PPE), such as the use of surgical masks and N95, N99, N100, PFF2 or PFF3, the use of an apron or overall, goggles and face shield, gloves and a hat. The entire team must receive training and demonstrate the ability to use PPE correctly and safely. Final considerations: The professional working in the pre-hospital care by ambulance is exposed to a series of occupational risks that need to be discussed and minimized through professional training.